The Development of Illustrated Pocket Book as a Source of Independent Learning in Sensory System Material in XIth Grade of High School Natural Science Program - Muliawati Muliawati; Binari Manurung; Diky Setya Diningrat (Magister Pendidikan Biologi, Universitas Negeri Medan, 2021)
Learning resources are a component needed in teaching and learning activities. One example of a learning resources often used by teachers and students is books. This study aims to develop a pocket book with a sensory system as a source of independent learning and to determine the effectiveness of a sensory system illustrated pocket book on student learning outcomes in the XIth Grade High School Natural Science Program. This type of research is Research and Development using the 4D Thiagarajan model (Define, Design, Development and Dissemination). The effectiveness test used a quasi experimental method with the pretest post-test control group design. The data obtained were both quantitative and qualitative. The results of the validation by material experts scored 95.9 (very feasible), language experts scored 90.77 (very feasible), and layout design experts scored 83.48 (very feasible). The results of the response by the Biology teacher were 99.58 (very feasible), and the results of student responses on individual tests were 97.78, small group tests were 98, and limited field tests were 99.72 under very feasible category. The effectiveness of sensory system illustrated pocket book is seen based on the students' Biology learning outcomes, t-test and N-gain value. The results showed that the sensory system illustrated pocket book as an independent learning resource was very feasible to use in biology learning and was quite effective in improving student learning outcomes in the XIth Grade of High School Natural Science Program.